STUDENTS’ EVALUATION OF THEIR AGENCY-BASED FIELD INSTRUCTION: Insights and Implications for Future Field Placements - Quilicol, Rosalie T. (Philippine Journal of Social Development; Vol 1 (2009): Philippine Journal of Social Development)
This paper reviews the University of the Philippines - Department of Social Work (UP-DSW) students’ evaluation of their agency-based fieldwork experiences for the period 2006-2008. The review focuses on the three elements of field instruction, namely:   the students, the agency, and field supervision. In general, the students rated their first field instruction course positively in terms of their perceived performance. The agencies were also favorably rated, with majority of the students saying that partnerships with these agencies were worth continuing. Likewise, students perceived that supervision provided by the faculty and agency supervisors was adequate.   The paper concludes with some points drawn from the review of the students’ evaluation that can enhance the effectiveness of the field instruction program.